The Effect of Implementing Smoke-Free Areas on Indoor Air Quality in Kulon Progo - Oktavian Denta; Haryono, Mahmuda Jundi; Musthofa, Arief; Baning, Theodola (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2024)
Background: The development of a city affects air pollution. Indonesia is the third country in the world with the highest number of smokers. Smoking behavior produces smoke that comes from chemicals and dust or particulate matter. Pollution in closed places also has a 2 – 5 times higher risk than in open places. In monitoring and evaluating compliance with smoke-free areas (KTR) in Kulon Progo in 2023, from 7 regions, it was found that there were 3 areas with low compliance, namely teaching and learning facilities, workplaces & public places. Aims: This research reveals the differences between places that comply and do not comply with the KTR Regional Regulation and their relationship with indoor air quality to prove whether the implementation of No-Smoking Areas influences indoor air quality. Method: Descriptive research method with quantitative analysis using SPSS. Primary data collection by observation refers to the KTR implementation monitoring checklist and air quality measurements using particulate dust meters and anemometers. Results: The results of the KTR sample data collection illustrate that KTR compliance has a positive effect on air quality with a significance value of 0.48. The dominant violations are the provision of ashtrays, the discovery of cigarette butts, and people smoking outside designated places, both indoors and outdoors. Findings of indoor violations greatly affect the levels of PM 2.5 and PM 10 in the air. Conclusion: Exposure to air pollution such as PM that exceeds the threshold can cause health problems and reduce productivity. So implementing optimal KTR regulations can improve indoor air quality. Consistency is needed from the person in charge of the area in supervision to increase compliance. Improving air quality is also expected to improve the health and productivity of students, employees, and the community.